Complex-Shaped Platinum Coils for Brain Aneurysms: Higher Packing Density, Improved Biomechanical Stability, and Midterm Angiographic Outcome - Wakhloo, A.K. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Five to 60% of coiled brain aneurysms recanalize, generally because of coil compaction. In vitro exclusive use of complex-shaped coils allows better packing of the aneurysmal sac and the neck as compared with helical coils. We report a single-center, prospective study using complex coils. Safety, packing density, and recanalization rate were evaluated. MATERIALS AND METHODS: Seventy-seven aneurysms were embolized using complex coils alone. Aneurysms had a volume of 265 mm(3) (diameter: 7.1 ± 3.3 mm) and a neck size of 4.1 ± 1.8 mm (range: 1.5–12 mm). Average follow-up available in 31 patients was 10.5 ± 7.6 months (range: 3–36 months). Primary angiographic endpoints included aneurysmal recanalization and (re)rupture. Primary adverse events included stroke or death. RESULTS: Complete or near-complete occlusion was achieved in all of the aneurysms but required balloon assistance in 24.6%. The packing density was computed as 37% ± 13%. No rerupture was observed during the follow-up interval. Recanalization was seen in 4 (12.9%) of 31. Two basilar tip aneurysms underwent a safe and complete recoiling. Periprocedural nondevice-related neurologic deficits were seen in 2 (2.9%) of 69 patients. CONCLUSIONS: The use of complex-shaped coils allows higher packing density, which may improve the recanalization rate. Basilar tip aneurysms remain a challenge.